Surface-Catalyzed Secondary Nucleation Dominates the Generation of Toxic IAPP Aggregates - Rodriguez Camargo, Diana C.; Chia, Sean; Menzies, Joseph; Mannini, Benedetta; Meisl, Georg; Lundqvist, Martin; Pohl, Christin; Bernfur, Katja; Lattanzi, Veronica; Habchi, Johnny; Cohen, Samuel IA; Knowles, Tuomas P. J; et al. (Frontiers in Molecular Biosciences, 2021)
The aggregation of the human islet amyloid polypeptide (IAPP) is associated with diabetes type II. A quantitative understanding of this connection at the molecular level requires that the aggregation mechanism of IAPP is resolved in terms of the underlying microscopic steps. Here we have systematically studied recombinant IAPP, with amidated C-terminus in oxidised form with a disulphide bond between residues 3 and 7, using thioflavin T fluorescence to monitor the formation of amyloid fibrils as a function of time and IAPP concentration. We used global kinetic analyses to connect the macroscopic measurements of aggregation to the microscopic mechanisms, and show that the generation of new aggregates is dominated by the secondary nucleation of monomers on the fibril surface. We then exposed insulinoma cells to aliquots extracted from different time points of the aggregation process, finding the highest toxicity at the midpoint of the reaction, when the secondary nucleation rate reaches its maximum. These results identify IAPP oligomers as the most cytotoxic species generated during IAPP aggregation, and suggest that compounds that target secondary nucleation of IAPP could be most effective as therapeutic candidates for diabetes type II.